Impact of Nitrogen Fertilizer Applications on Surface Water Nitrate Levels within a Kenyan Tea Plantation - J. K. Maghanga; J. L. Kituyi; P. O. Kisinyo; W. K. Ng’etich (Journal of Chemistry)
Tea production in the Kenyan Rift Valley uses high rates of nitrogenous fertilizer. Nitrates can be discharged to water bodies through leaching and surface run-off. Nitrate levels above 10 mg/L NO3-–N cause methemoglobinemia which is fatal. A study to monitor changes in surface water nitrate levels was carried out in ten rivers within a Kenyan tea plantation for three years. Water samples were obtained before and after fertilizer application in 2004, 2005, and 2006. Nitrate-nitrogen (NO3-–N) was determined colorimetrically by the cadmium reduction method using HACH-DR 2400 dataloging spectrophotometer. For the three years, the highest nitrate-nitrogen levels were in river Temochewa in 2005 during the first fertilizer applications (4.9 mg/L to 8.2 mg/L). There was no established trend between surface water nitrate levels and the time of fertilizer applications; however, fertilizer application contributed to an increase in nitrate levels. The initial nitrate-nitrogen levels in most of the rivers were high, indicating that contamination could have been upstream; hence, further research is required to establish this. Nitrogen-nitrogen levels in the three years were below the maximum contaminant level of 10 mg/L NO3-–N; however, the rivers should be monitored frequently.